Nutrient uptake by competing roots in soil - Baldwin, J; Baldwin, John Paul (1972)
﻿ It is postulated that definition of the availability of nutrients in soil t for plant uptake, will not be satisfactory, unless there is consideration of the plant's role as the absorber. The amount of nutrients absorbed by plants from soil can be related to i) the initial concentration in the soil solution, ii) the capacity of the soil to maintain this concentration (the buffer power), iii) the ease of movement of the nutrient to an absorbing root, and iv) the plant demand. These ideas are the foundation of models which successfully describe the nutrient uptake by single roots, growing in an infinite quantity of soil. The aim of the present work was to extend the approach used to explain uptake by single roots, to complete root systems. The requirements for the work are: a theoretical description of nutrient flow to an absorbing, multiple root system experiments for examining the proposed hypotheses. When a root absorbs a nutrient, there is a depletion in the nutrient concentration at the root surface. In a system of many roots, the zones of nutrient depletion around each root overlap. This reduces the effective initial concentration in the soil solution. So, in a multiple root system, the soil around each root is limited. The extent of overlap depends on the diffusion coefficient of the nutrient, the plant demand, and the interroot distance. The consequence is a lowering of the concentration at each root surface, below that of a similar root absorbing alone. An electrical analogue (Sanders et al. 1971) of diffusion of solutes to groups of absorbing roots was used to simulate nutrient uptake by plants from soil. The analogue was particularly useful for investigating the general consequences of different plant and soil conditions. To interpret specific plant uptake data, a more flexible computer model of diffusion and mass flow to a root system of variable density, with any specified uptake properties, was developed. For workers interested in an accuracy of andplusmn; 20%, an equation for calculating uptake, by systems similar to those which the computer model treats, is presented, which can be solved on a desk calculator. To test the model, experimental data on nutrient uptake, root dimensions and distribution, and soil conditions, during the growth of whole plants in soil was obtained. The computer model predicted the measured plant uptake wall, when values of the plant demand coefficient (which related uptake rate to the external solution concentration) given is the literature, from solution culture work under similar conditions, were used. It is concluded that the theory is an adequate representation of the simple plant-soil system used in the experiments. The expression, relating plant demand to concentration in the soil solution, was simulated on the electrical analogue. The effects of pattern, density, radius and demand coefficient of roots, on the course of uptake of solutes, of varying degrees of mobility, were investigated. Quantitative interrelations between soil and plant characteristics were established, which are discussed in the light of earlier concepts of mobility and availability of nutrients in soil. The uptake of a solute by any root system is roughly determined by the plant demand coefficient and the product of the solute diffusion coefficient, D, the absorption time, t, and the root density, L. The product DtL, for potassium, may often be is the range where root pattern affects uptake. This can be estimated graphically. Theory suggests that the uptake rate of K and K is the plant experiments was reduced by interroot competition. In both experiments, if supply was by physical processes only, the plants were absorbing K from the soil near to a maximum rate, which was set by transport through the soil. In those circumstances, the rate of uptake into a plant is limited by the length of root. Movement through the soil was easily able to supply the plant's requirement of N, until the total quantity was exhausted. It is deduced that this will usually be the case in British arable soils. A major problem, in the experimental determination of plant uptake from soil, results from the inaccessibility of the roots. A technique was devised for estimating the length and pattern of living roots of individual plants, without excessive labour. Radioactive roots are detected by autoradiography as they intersect planes of soil, and the root length par unit volume and rooting pattern follow easily. If two plants are labelled with different isotopes, their root systems can be distinguished. Any spatial interactions between the root systems are detected by the method, and the causes can be inferred. If the roots are extracted from the soil, their length can be automatically measured with an Image Analysing Computer.